2010
DOI: 10.1007/s10637-010-9402-x
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin induces human mucoepidermoid carcinoma Mc3 cells apoptosis in vitro and in vivo

Abstract: Mucoepidermoid carcinoma (MEC) is the most common malignant tumor in salivary glands and high-grade MEC in particular demonstrates little response to chemotherapy which has been used largely for palliative treatment of metastatic disease. Baicalin, one of the main active compounds of Scutellaria baicalensis, possesses anti-inflammatory, antioxidant and antitumor properties. In the present study, we investigated the growth inhibiting and apoptosis-inducing effects of baicalin on a highly metastatic human mucoep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…[7273] Cells from a variety of human malignancies have a decreased ability to undergo apoptosis in response to some physiological stimuli. Induction of apoptosis in malignant cells may therefore represent a promising approach to both chemoprevention and chemotherapy, and searching for agents that can specifically trigger apoptosis in tumor cells has become an attractive strategy in anticancer drug discovery.…”
Section: Flavonoids As Potent Anticancer Agentsmentioning
confidence: 99%
“…[7273] Cells from a variety of human malignancies have a decreased ability to undergo apoptosis in response to some physiological stimuli. Induction of apoptosis in malignant cells may therefore represent a promising approach to both chemoprevention and chemotherapy, and searching for agents that can specifically trigger apoptosis in tumor cells has become an attractive strategy in anticancer drug discovery.…”
Section: Flavonoids As Potent Anticancer Agentsmentioning
confidence: 99%
“…It is considered to be one of the effective and safe drugs widely used in Asia for the treatment of a variety of diseases, such as brain diseases, hepatic disorders, inflammatory diseases, and so on. Furthermore, it has been reported that baicalin has multiple biologic functions, including anti-inflammatory, antioxidant, antiapoptotic, and immune regulation properties (Xu et al, 2011;Yin et al, 2011;Hou et al, 2012). There is increasing evidence to support the notion that this compound may have potential roles in anti-inflammation and immune regulation (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites were chosen for their demonstrated bioactivity in diverse cellular processes like apoptosis and angiogenesis. For example, acteoside has been shown to inhibit human promyelocytic HL-60 leukemia cell proliferation via inducing cell cycle arrest at G 0 /G 1 phase and differentiation into monocyte (Lee et al 2007), oroxylin A has been shown to induce apoptosis in cancer cells via p53 and therefore is a potential candidate for cancer therapy (Mu et al 2009), and baicalin has been shown to induce apoptosis in human mucoepidermoid carcinoma Mc3 cells in vitro and in vivo (Xu et al 2010). Chrysin has been shown to suppress IL-6-induced angiogenesis via down-regulation of JAK/STAT3 and VEGF in vitro and in vivo (Lin et al 2010), and wogonoside can inhibit lipopolysaccharide-induced angiogenesis in vitro and in vivo via toll-like receptor 4 signal transduction (Chen et al 2009).…”
Section: Introductionmentioning
confidence: 99%